National Action plan for Agriculture GHG Inventory Improvement: Trinidad & Tobago - Stevens, Luanne (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
The IICA-GCF Readiness Project aims to enhance climate action in the agricultural sector in nine CARICOM sub-region countries by strengthening policies, capacities, frameworks, methods, and institutional arrangements for MRV and analyzing agricultural data. The project also aims to identify bankable projects and disseminate best practices for building climate-resilience in prioritized agricultural value chains. In Trinidad & Tobago, the government is transitioning, and the project aims to improve the agriculture GHG inventory by assessing the status, identifying areas for improvement, developing actions, and prioritizing them.